2021
DOI: 10.1002/lsm.23440
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Topical Silymarin Versus Low Fluence 1064‐nm Q Switched Nd:YAG Laser in the Treatment of Melasma: A Comparative Randomized Trial

Abstract: Background and Objectives The management of melasma is challenging and requires multiple uses of available therapeutic options. To compare the short‐term efficacy and safety of topical silymarin and low fluence 1064‐nm Q‐switched ND:YAG laser for treatment of melasma with dermoscopic follow‐up. Study Design/Materials and Methods Fifty female patients with melasma were included in this study. They were randomly divided into two groups. Group A: 25 patients were treated with six sessions of low fluence Q switche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Severe adverse events were rarely reported in both treatment groups [ 46 ]. In a study comparing LFQSNY and topical silymarin cream, there was no significant difference in the reduction in mMASI score and the incidence of adverse effects in both groups [ 14 ]. Dev T. et al reported that there was no significant difference in the reduction in mMASI, MI score, and subjective evaluation of patients between LFQSNY and TC cream [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Severe adverse events were rarely reported in both treatment groups [ 46 ]. In a study comparing LFQSNY and topical silymarin cream, there was no significant difference in the reduction in mMASI score and the incidence of adverse effects in both groups [ 14 ]. Dev T. et al reported that there was no significant difference in the reduction in mMASI, MI score, and subjective evaluation of patients between LFQSNY and TC cream [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…This new technique has been used with LQSNY (<3 j/cm 2 ), 1–2 weeks treatment intervals, increased treatment passes, and large spot size and leads to less inflammation and adverse effects 10 . The use of LQSNY has been proven to be an effective and safe therapy for moderate to severe dermal and mixed‐type melasma by decreasing the number of melanosomes, reducing the expression of melanogenesis‐associated proteins (TRP‐1 and TRP‐2), and reducing melanogenic stimulators (α‐MSH and NGF) 26,27 . Besides, LQSNY stimulates collagen formation along with the resulting dermal damage, allowing for brighter and tighter skin 28 .…”
Section: Discussionmentioning
confidence: 99%
“…10 The use of LQSNY has been proven to be an effective and safe therapy for moderate to severe dermal and mixed-type melasma by decreasing the number of melanosomes, reducing the expression of melanogenesis-associated proteins (TRP-1 and TRP-2), and reducing melanogenic stimulators (α-MSH and NGF). 26,27 Besides, LQSNY stimulates collagen formation along with the resulting dermal damage, allowing for brighter and tighter skin. 28 Although melanin absorbs less LQSNY than green and red light lasers, this longer wavelength can penetrate deeper skin without damaging the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining a P value < 0.05 supports statistically significant differences. The Mann–Whitney test is used for comparison between two groups having quantitative variables that are not normally distributed [ 86 ]; likewise, it is a robust competitor of the t-test in the univariate setting [ 87 ].…”
Section: Methodology and Methodsmentioning
confidence: 99%